Evaluating Severity of Malocclusion and Oral Health Status and Its Correlation with Socioeconomic Status in Population - Nanjannawar, Lalita Girish; Kumar Bhatnagar, Tarun; Ray, Asmita; Akshay Rathi, Vyom; Panjwani, Jyoti; Chaudhary, Varunjeet (Journal of Neonatal Surgery, 2025)
Background Malocclusion and poor oral health are prevalent public health concerns, often influenced by socioeconomic status (SES). Socioeconomic disparities can significantly impact access to dental care, awareness, and timely intervention, potentially exacerbating the severity of malocclusion and deteriorating oral health status. This study aimed to evaluate the severity of malocclusion and oral health status in a defined population and analyze its correlation with varying socioeconomic levels. Materials and Methods A cross-sectional study was conducted on 500 individuals aged 12–35 years from urban and rural areas. The severity of malocclusion was assessed using the Index of Orthodontic Treatment Need (IOTN), while oral health status was evaluated using the DMFT (Decayed, Missing, Filled Teeth) index and Community Periodontal Index (CPI). Socioeconomic status was determined using a modified Kuppuswamy scale. Data were analyzed using SPSS version 25.0, applying Pearson’s correlation and Chi-square tests to determine associations between SES, malocclusion severity, and oral health parameters. Results Out of 500 participants, 45% demonstrated a high need for orthodontic treatment (IOTN Grade 4-5). The mean DMFT score was 4.2 ± 1.6, and 38% showed CPI scores indicating moderate to severe periodontal conditions. A significant negative correlation was observed between socioeconomic status and both malocclusion severity (r = -0.42, p < 0.001) and poor oral health indicators (DMFT: r = -0.35, p = 0.002; CPI: r = -0.39, p = 0.001). Participants from lower socioeconomic groups exhibited higher malocclusion severity and poorer oral health compared to those from higher socioeconomic strata. Conclusion The study highlights a strong correlation between lower socioeconomic status and increased severity of malocclusion alongside deteriorated oral health status. These findings emphasize the need for targeted public health strategies, including accessible orthodontic and preventive dental care programs, particularly for socioeconomically disadvantaged populations